Winter Construction Measures for Roadbed - Sun, Jian (Journal of Theory and Practice of Engineering Science, 2023)
In recent years, China has made obvious achievements in roadbed construction, which cannot be separated from the efforts of relevant staff. China has completed the construction of many modern roadbed roads, and there have been many advancements in related roadbed construction technologies. This not only strengthens communication between different regions, improves the convenience of people's daily travel, but also further narrows the gap between China and other developed countries. However, there are still many key points to face when designing the roadbed, especially in the construction of the roadbed and pavement, which are still worth studying. The characteristics of winter climate will have a certain impact on roadbed construction. For this purpose, specific construction measures for winter roadbed construction will be explored to ensure the quality of roadbed construction in winter, for reference.